The Effects of Inclusive Education on the Self-Concept Of Students with Special Educational Needs - Nurul Aina Zakaria; Mohd Mokhtar Tahar (Journal of ICSAR, 2017)
Inclusive education is a platform that provides opportunities for students with special educational needs (SEN) to learn in a regular classroom with normal students. However, there are many challenges faced by students with SEN who learn in an inclusive setting, such as negative perception from the mainstream teachers and peers, being bullied and excluded by peers; facing academic issues because of following the regular curriculum like normal students, and lack of support from the parents. The problems occurred has affected the self-concept of students with SEN. Therefore, a study was conducted to explore the impact of inclusive education towards the self-concept of students with SEN in terms of identify the level of self-concept among students with SEN; identify the strongest and the weakest domains of self-concept; explores the differences of self-concept levels based on gender; and to study the relationship between the level of self-concept with the period of learning in an inclusive education. The respondents consisted of 52 students with SEN, aged between 8 to 15 years old who learn in inclusive settings from 10 schools in the district of Hulu Langat, Selangor. The study was conducted using a set of questionnaires that contains 80 items of Piers-Harris Children’s Self Concept Scale that respondents had to answer. The findings showed that the level of self-concept among the students with SEN is at moderate. The study also found that the strongest self-concept domain among the students with SEN is Happiness and Satisfaction (HAP), and the weakest self-concept domain is Popularity (POP). In addition, the results showed that there is no significant difference in the levels of self-concept based on gender, and there is no significant relationship between the levels of self-concept with learning periods in inclusive education.